S41 Conductance-Derived Right Ventricular Stroke Work Measured by Pressure Volume Loops in Chronic Thromboembolic Pulmonary Vascular Disease. (19th November 2012) - McCabe, C; Taboada, D; Mackenzie-Ross, R; Harvey, I; Sheares, K; White, P; Axell, R; Hoole, S; Shapiro, L; Pepke-Zaba, J
Abstract : Background: The most significant determinant of both symptoms and survival in pulmonary arterial hypertension (PAH) is the degree of cardiac impairment that results from increased right ventricular after load.[1] Resting haemodynamic parameters however do not always correlate with exercise symptoms and performance limitation. Pulmonary vascular resistance (PVR) is normally measured at rest and is derived from mean flow data. This fails to take into account both the pulsatile nature of flow in the pulmonary artery and thus pulmonary arterial compliance.[2] Chronic thromboembolic pulmonary hypertension (CTEPH) lies within Group IV of the Dana Point 2008 Classification and arises from persistent pulmonary vascular occlusion secondary to arterialthrombus. However, for unclear reasons a proportion of patients with significant thrombus burden do not develop elevation of pulmonary arterypressures creating a two compartment model of disease. Precise haemodynamic abnormalities are likely to be determined by several factors including thrombuschronicity, load, distribution, pulmonary artery compliance and right ventricular adaptation in response to increased after load though there is no discernible relationship between routinely measured haemodynamics and any of these parameters. Furthermore, the effect of right ventricular performance on exercise capacity remains poorly characterised in this disease subgroup. Aims and Methods: We hypothesise that exercise capacity in ourpatient cohort ultimately depends on the adaptation of both right ventricle and pulmonary arteries to thrombotic insult. Using a conductance-based pressure volume approach at the time of right heart catheterisation, we measured the right ventricular mechanoenergetics in six patients (2 female) with chronic pulmonary vascular occlusion but different resting haemodynamics. These results were compared with peak exercise oxygen consumption assessed by contemporaneous cardiopulmonary exercise testing. Results and Conclusions: Peak exercise capacity (peak V02 )was inversely related to PVR throughout our patient group (p=0.046). The close association between PVR and right ventricular stroke work index (RVSWI)(r=0.96), derived from the area within the pressure volume loop (Fig 1 ), suggests an increased resting stroke work may result in earlier cardiovascular limitation at peak exercise in those with more severe pulmonary hypertension. This seems physiologically compatible given the greater after load seen with more severe pulmonary hypertension and diminished cardiac reserve. Initial analysis of isovolumic relaxation indices (Tau, dP/dtmin ) suggest pulmonary hypertension is not mediated by diastolic dysfunction within the right ventricle and may be more related to reduced pulmonary artery compliance(Ea). The impaired right ventricular stroke work for low/normal PVR fits with patient symptoms and provides insight into the early stages of the process of right ventricular failure. Girgis RE Predicting long term survival in pulmonary arterial hypertension JACC 2011 58 24 p2520. Chesler et al. How to measure pulmonary vascular and right ventricular function. Conf Proc IEEE Eng Med Biol Soc 2009 p177.